Telogen effluvium as the first symptom of Crohn’s disease in a child - Rogalidou, Maria (Hellenic Society of Gastroenterology, 2014)
Crohn’s disease usually manifests gastrointestinal symptoms, however in some cases the patient presents with prominent or even exclusive extraintestinal involvement. Alopecia has been reported as a complication of therapeutic agents used in the treatment of inflammatory bowel disease, and, in a few cases of adult patients, prior to the appearance of gastrointestinal symptoms. We present a 10 year-old-child with telogen effluvium that appeared one year before the diagnosis of Crohn’s disease, as the first and only symptom at that time. Other systemic causes of hair loss such as micronutrient deficiencies, endocrine imbalance or chemical exposure were excluded. Eight months later the patient presented with mild iron deficiency and signs of social retraction, while two months before the final diagnosis of Crohn’s disease other more characteristic alarming symptoms (mild fever, oral apthous ulcers, weight loss) were added to the clinical picture. Alopecia improved after remission of Crohn’s disease, reappeared when the patient relapsed, and finally resolved gradually when complete remission of Crohn’s disease was achieved. Telogen effluvium was the first symptom of Crohn’s disease in a child, and, although this is a rare association, it should be considered as an extraintestinal manifestation of Crohn’s disease.